Comparison of energy and micronutrient intake and their adequacy between different socio economic zones of Metropolitan Tehran - Salehi, Forouzan; Kalantari, Naser; Asadilari, Mohsen; Abdollahi, Morteza; Ajami, Marjan (Progress in Nutrition, 2019)
Background: Micronutrient deficiency is a major health problem in many countries. The purpose of this study is to assess and compare the adequacy of energy and micronutrient intake within five different zones of Tehran. Methods: This is a cross-sectional study that was conducted from September to December 2007 in all 22 districts of the municipality of Tehran. A 24-hour Recall questionnaire was completed by experienced interviewers. The micronutrient requirements of household members were calculated and determined using the FAO / WHO table. Results: The average energy intake in the South of Tehran is 2491 (2469-2513) Kcal/person/day. In the West it is 2525 (2467-2583) Kcal/person/day, these values being higher than the three remaining zones (P < 0.001). The highest calcium intake of 960 (921.59-997.6) mg/person/day was found in the Center zone, with the lowest value of 799 (776.0-823.2) mg/person/day found in the South, (P < 0.001). The highest intake of riboflavin is in the Center, at 1.6 (1.28-1.31) mg/person/day, and the lowest intake is in South, at 1.3 (1.28-1.31) mg/person/day. The highest intake of vitamin C was shared between the North and Center at150 (141.0-159.0) mg/person/day with the lowest consumption seen in South, 119 (116.0-121.1) mg/person/day. The highest consumption of vitamin A was in Center at 1420 (1296.5-1543.0) mg/person/day and the lowest consumption was in South at 937 (906.0-969.0)mg/person/day.Conclusion: Despite the high energy intake of the South and the West zones, micronutrient deficiency is quite prevalent, representing the major impact of social and cultural factors independent of economic factors.